1995
DOI: 10.4319/lo.1995.40.4.0649
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin production in marine algae. 1. An interspecies comparison

Abstract: Phytochelatins are metal-binding peptides produced enzymatically by higher plants, fungi, and algae in response to many metals, particularly Cd. We have studied phytochelatin production in several marine phytoplankton exposed to a range of free Cd ion concentrations. As a result of increased analytical resolution, we have found that all the species contain phytochelatin, even when there is no added Cd, and that elevated phytochelatin concentrations are induced by Cd, even at very low and environmentally releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(116 citation statements)
references
References 19 publications
2
111
2
Order By: Relevance
“…Copper concentrations have been shown to affect community composition in coastal ecosystems (26); therefore, it came as some surprise to find that Ostreococcus lacks a gene for phytochelatin synthase for ameliorating copper toxicity (27,28). Instead, this organism contains tesmin-like metallothionein sequences and several Cu-efflux proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Copper concentrations have been shown to affect community composition in coastal ecosystems (26); therefore, it came as some surprise to find that Ostreococcus lacks a gene for phytochelatin synthase for ameliorating copper toxicity (27,28). Instead, this organism contains tesmin-like metallothionein sequences and several Cu-efflux proteins.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli, which lack a vacuole, translocate Cd to their membranes (35) by binding Cd with glutathione, a precursor of (and functionally analogous to) phytochelatin (28). Cd is a particularly efficient metal for inducing production of metal-binding ligands in plankton (36), with analysis of field populations (37,38) and laboratory cultures (39,40) demonstrating that Cdbinding ligands are produced far in excess of that needed to sequester any intracellular Cd (and other metals, such as Cu and Zn; ref. 36).…”
Section: Discussionmentioning
confidence: 99%
“…Rice plants exposed to 35 Scysteine or 9 × 10 -8 M 109 Cd in solution for 24 h accumulated 109 Cd and 35 S in the same low molecular weight soluble fraction of roots (Dabin et al 1978), which might have contained phytochelatins, glutathione or other sulphur compounds complexed with Cd. Using a sensitive technique for phytochelatins, Ahner et al (1995) have shown that concentrations of Cd 2+ as low as 10 -12 M induced the synthesis of phytochelatin in several species of marine phytoplankton. In the studies of Tukendorf and Rauser (1990) and Ahner et al (1995) the binding of Cd to the phytochelatins was not demonstrated.…”
mentioning
confidence: 99%
“…Using a sensitive technique for phytochelatins, Ahner et al (1995) have shown that concentrations of Cd 2+ as low as 10 -12 M induced the synthesis of phytochelatin in several species of marine phytoplankton. In the studies of Tukendorf and Rauser (1990) and Ahner et al (1995) the binding of Cd to the phytochelatins was not demonstrated. The role of phytochelatins in the accumulation of Cd in crops exposed to low Cd levels remains to be clarified.…”
mentioning
confidence: 99%